2022
DOI: 10.3390/ijms23169208
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Genetic Features and Antimicrobial Susceptibility of Pseudomonas aeruginosa Strains Isolated from Bloodstream Infections

Abstract: Pseudomonas aeruginosa is a Gram-negative rod and an etiological factor of opportunistic infections. The infections of this etiology appear mostly among hospitalized patients and are relatively hard to treat due to widespread antimicrobial resistance. Many virulence factors are involved in the pathogenesis of P. aeruginosa infection, the coexistence of which have a significant impact on the course of an infection with a particular localization. The aim of this study was to assess the antimicrobial susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
(64 reference statements)
1
3
1
Order By: Relevance
“…This study identified the plC N gene in 100% of the MDR strains and in 87.8% of the MDS strains, while the gene encoding the synthesis of hemolytic phospholipase C was identified in 96.5% and 83.8% of the strains, respectively. The results are quite similar to the values obtained in our previous study on bloodstream-derived isolates, where the presence of the plC N and plC H genes was detected in 95.8% and 100% of the strains, respectively [ 22 ]. Meanwhile, Gonçalves et al [ 23 ] identified a lower prevalence of the plC N gene among carbapenem-resistant strains (88.0%) compared to the results of this work.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study identified the plC N gene in 100% of the MDR strains and in 87.8% of the MDS strains, while the gene encoding the synthesis of hemolytic phospholipase C was identified in 96.5% and 83.8% of the strains, respectively. The results are quite similar to the values obtained in our previous study on bloodstream-derived isolates, where the presence of the plC N and plC H genes was detected in 95.8% and 100% of the strains, respectively [ 22 ]. Meanwhile, Gonçalves et al [ 23 ] identified a lower prevalence of the plC N gene among carbapenem-resistant strains (88.0%) compared to the results of this work.…”
Section: Discussionsupporting
confidence: 90%
“…Our study reported the presence of the nan1 gene in 28.1% of the MDR and in 31.1% of the MDS strains. Our previous study identified the prevalence of the nan1 gene at a much higher level, occurring among 47.9% of the strains isolated from bloodstream infections, with variable levels of resistance to selected antibiotics [ 22 ]. It is noteworthy that the clinical samples in the previous study were also derived from patients at the same hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes that encode for pilin structural subunits (pil A and pil B) were also detected, the results of the molecular analysis of 25 isolates showed that the percentage of the pil B gene was (4%), and only one isolate was positive for this gene, the result is inconsistent with the result of Bogiel who showed that the lowest frequency of pil B gene was ranged (4.2_4. While the result of gene pil A was (92%), these results disagreed with the results obtained by (Bogiel et al, 2021(Bogiel et al, , 2022 who showed the frequency of pil A gene ranged from (19.7-to 15.9) %, this finding is very interesting because it suggests that the presence of this specific gene is essential for the colonization or infection of the human gastrointestinal tract, therefore, it might be a correlation between the presence of the chosen virulence genes and P. aeruginosa ability to form biofilm or colonize a specific location, but more studies are required to confirm this result (Bogiel et al, 2021), Figure (6)..…”
Section: Resultscontrasting
confidence: 83%
“…The genes pilB and pilA encode components of the type IV pili (T4P) system in many bacteria, including P. aeruginosa. Only one strain expressed the pilB gene (5.26%), and some strains had the pilA gene (36.84%), which was expected given the low prevalence of this gene; their expression also varies with the infection type [68][69][70][71][72][73]. Both genes are required for type IV pili formation and function.…”
Section: Detection Of Virulence Genesmentioning
confidence: 94%